Pengaruh Online Customer Reviews, Live Streaming, dan Affiliate Marketing terhadap Impulse Buying melalui Customer Trust Parfum Evangeline pada Pengguna TikTok Shop di Indonesia - Anggraeni, Alfina Fatika; Hariyadi, Guruh Taufan; Pakarti, Piji; Fatmawati, Elia Resha (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study investigates the influence of Online Customer Reviews, Live Streaming, and Affiliate Marketing on Impulse Buying behavior, mediated by Customer Trust. Employing a quantitative methodology with SmartPLS 4.0 analysis, the research reveals that these three digital marketing variables exert a positive and significant effect in fostering consumer trust and prompting unplanned purchases. In particular, Affiliate Marketing stands out as the predominant predictor of impulsive buying. The analysis of indirect effects confirms that Customer Trust functions as a partial mediator, amplifying the influence of marketing strategies on Impulse Buying. These results underscore that, in addition to technical marketing elements, cultivating customer trust is essential for enhancing impulsive purchasing decisions within digital platforms.